CHANGES IN THE PANCREAS IN TRAUMATIC BRAIN INJURY - Oblokulova O.A. (Western European Studies, 2025)
Traumatic brain injury (TBI) is one of the most common and severe conditions that can cause systemic disorders in the body. Against the background of TBI, changes are observed not only in the nervous system, but also in the endocrine and digestive systems. The pancreas, which has both exocrine and endocrine functions, is particularly vulnerable to neurohumoral shifts and metabolic disorders that occur after brain injury. The purpose of this work is to consider the pathogenetic mechanisms and clinical manifestations of pancreatic changes in traumatic brain injury, as well as to identify areas for the diagnosis and treatment of such disorders
Keywords: Traumatic Brain Injury; Pancreas; Pancreatitis; Hyperglycemia